The quality of service assessment of eMBB and mMTC traffic in a clustered 5G ecosystem of a smart factory - Viacheslav Kovtun; Oksana Kovtun; Krzysztof Grochla; Oleh Yasniy (Egyptian Informatics Journal)
Industry 4.0 demands seamless integration of smart factories with the Industrial Internet of Things (IIoT), reliant on robust communication infrastructure. Leveraging 5G’s support for enhanced Mobile Broadband (eMBB), massive Machine Type Communication (mMTC), and Network Slicing (NS), this study explores quality of service assurance within a clustered 5G ecosystem of a smart factory. The article proposes two new multi-parameter scenarios for allocating the entire channel pool between different types of requests (mMTC, eMBB) for the model of an integrated open 5G cluster. The scenario with isolation does not allow channel reassignment between requests of different types or originating zones (handover or from the coverage area of the target 5G cluster), while the virtual scenario allows such reassignment. It is shown that using these scenarios, the stationary distribution of probabilities of states of the corresponding two-dimensional Markov chains has a multiplicative form. An information technology has been developed to calculate QoS indicators for different types of requests using these channel allocation scenarios. Studies have been conducted on the effectiveness of using one or another access strategy depending on the loads on the 5G cluster. Based on the proposed mathematical apparatus, the information technology enables finding the optimal scenario for channel allocation, as well as calculating the parameters’ values for such a scenario.